Secure Certificateless Signature with Revocation in the Standard Model. (19th November 2014) - Tsai, Tung-Tso; Huang, Sen-Shan; Tseng, Yuh-Min
Abstract : Certificateless public key cryptography is very attractive in solving the key escrow problem which is inherent in identity- (ID-) based public key cryptography. In the past, a large number of certificateless cryptographic schemes and protocols were presented, but a secure certificateless signature in the standard model (without random oracles) is still not accessible until now. To the best of our knowledge, all the previously proposed certificateless signature schemes were insecure under a considerably strong security model in the sense that they suffered from outsiders' key replacement attacks or the attacks from the key generation center (KGC). In this paper, we propose a certificateless signature scheme without random oracles. Moreover, our scheme is secure under the strong security model and provides a public revocation mechanism, called revocable certificateless signature (RCLS). Under the standard computational Diffie-Hellman assumption, we formally demonstrate that our scheme possesses existential unforgeability against adaptive chosen-message attacks.